2015
DOI: 10.1111/aji.12408
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cells: Key Players in Endometriosis

Abstract: Endometriosis affects more than 10% of women, causing significant pain and morbidity. It is also a significant cause of infertility. The aetiology of the disease remains an enigma, and the mechanisms responsible for the associated infertility are unclear. A role for immune cells in endometriosis has been postulated, with attention directed towards natural killer (NK) cells and macrophages. NK cells kill tumours and infected cells but also have roles in tissue remodelling in several organs including the uterus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 104 publications
(190 reference statements)
1
81
1
4
Order By: Relevance
“…Consequently, decreased expression of both SIGIRR and CEACAM-1 genes in ectopic tissues may explain the dysregulated inflammatory cytokine elevation and T-cell activation observed in endometriosis patients. Furthermore, decreased expression of NFIL3 (32), IL15 (33), and GNLY (34) in ectopic lesions support diminished cytotoxicity of NK and CD8+ T cells in women with endometriosis toward autologous endometrial fragments (35, 36). The expression of genes involved in signaling pathways, including TRAF4, MAPK1 , and DUSP4 , were significantly decreased in expression in ectopic tissues compared with control endometrium.…”
Section: Discussionmentioning
confidence: 83%
“…Consequently, decreased expression of both SIGIRR and CEACAM-1 genes in ectopic tissues may explain the dysregulated inflammatory cytokine elevation and T-cell activation observed in endometriosis patients. Furthermore, decreased expression of NFIL3 (32), IL15 (33), and GNLY (34) in ectopic lesions support diminished cytotoxicity of NK and CD8+ T cells in women with endometriosis toward autologous endometrial fragments (35, 36). The expression of genes involved in signaling pathways, including TRAF4, MAPK1 , and DUSP4 , were significantly decreased in expression in ectopic tissues compared with control endometrium.…”
Section: Discussionmentioning
confidence: 83%
“…With regard to endometriosis, the cytotoxic function is reduced in peripheral and peritoneal NK cells. [53][54][55][56][57] Due to diminished cytotoxicity, retrograde endometrial cells are prone to survive in the peritoneal cavity, which results in the development of endometriosis. Factors controlling NK cell function have not been thoroughly investigated; however, several studies have shown that IL-6, 57 IL-15, 58 and transforming growth factor-β1 59 suppress NK cell cytotoxic activity.…”
Section: Reduced Nk Cell Cytotoxic Activity In Endometriosismentioning
confidence: 99%
“…With regard to endometriosis, the cytotoxic function is reduced in peripheral and peritoneal NK cells . Due to diminished cytotoxicity, retrograde endometrial cells are prone to survive in the peritoneal cavity, which results in the development of endometriosis.…”
Section: Introductionmentioning
confidence: 99%
“…NK cells have a decreased expression of inhibitory KIRs, including KIR3DL1 (also known as NKB1) and KIR2DL3 (also known as GL183), on their surface and have enhanced cytotoxic functions. In endometriosis, peripheral NK cells and peritoneal NK cells exhibit an increased expression of KIRs and have reduced levels of cytotoxicity (63). Endometriotic cells develop several strategies to escape immune surveillance to avoid attack from the immune system.…”
Section: Functional Pathways Of Adenomyosis Candidate Genesmentioning
confidence: 99%